Spiritual-Instructional Leadership: Reframing Academic Supervision for Educational Quality in a Pesantren-Based Madrasah - Zainal Abidin; Ahmad Qusairi; Ikmal Wahyudi (JUMPA : Jurnal Manajemen Pendidikan, 2026)
This study analyses how academic supervision is enacted as an instructional leadership practice to improve educational quality in a pesantren-based madrasah, a context that remains underexplored despite its distinctive integration of formal schooling and religious formation. Using a qualitative single-case study design at Madrasah Tsanawiyah Darullughah Wadda'wah (MTs DALWA) Bangil, Pasuruan, data were gathered through in-depth interviews with the principal, the vice-principal, and six teachers, alongside non-participant observation and documentation study, and analysed using the interactive model of Miles, Huberman, and Saldaña with source and technical triangulation. The findings show that supervision is conducted systematically across three stages, namely participatory planning, dialogic classroom observation and feedback, and evaluation tied directly to teacher professional development, functioning as continuous professional development rather than administrative control. The study's central contribution is the identification of a Spiritual-Instructional Leadership model, in which supervisory legitimacy derives not only from the principal's managerial position but from religious authority embedded in the pesantren. This spiritual legitimacy, expressed through the ethic of mutual learning (mudzakarah), converted initial teacher resistance into collaborative engagement, demonstrating that Western-derived instructional leadership frameworks require contextual reworking in faith-based settings. The study contributes to educational management theory and offers practical guidance for the Indonesian Ministry of Religious Affairs (Kemenag), showing how pesantren-based madrasahs can operationalise academic supervision in ways that respect local religious-cultural norms while meeting national quality standards.